The Impact of Teaching Aids on Learning and Development of Preschool Children in Luangprabang District - Vannapha, Phetsanti; Phayyavong, Somchai; Thiphaphone, Kinnaly; Phanthong, Bounlai (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The current state of teaching and learning among early childhood educators reveals that the use of instructional media lacks variety. Furthermore, some teachers still lack the skills to produce media that aligns with children's developmental stages, which directly impacts the interest and learning outcomes of preschool children. Consequently, the researcher was interested in studying the state of instructional media usage among teachers in kindergartens within Luang Prabang City, Luang Prabang Province.The objectives of this research were to study the state of instructional media usage for preschool children among teachers in kindergartens in Luang Prabang City, Luang Prabang Province.The methodology involved collecting data from teachers across 33 kindergartens in Luang Prabang City, with a target group of 150 female teachers. The research instrument was a questionnaire covering four key areas: 1) teachers' understanding of using instructional media, 2) the importance of using instructional media, 3) the results of using instructional media, and 4) the production of instructional media. Data were analyzed using the SPSS program to determine the Mean () and Standard Deviation (SD). The research findings indicated that the state of instructional media usage to enhance preschool children's development among teachers in Luang Prabang City was at a high level across all dimensions. Specifically, the highest mean score was found in teachers' understanding of media usage, while the lowest mean score was in the area of instructional media production.